Innovative hypoglycaemia care pathway for admission avoidance: a partnership approach with a local ambulance trust. (15th May 2013) - James, June; Fairfield, Jane; De Groot, Louise; Jackson, Steve
Abstract: In 2010, Leicester City Primary Care Trust commissioned an Intermediate Care Diabetes Service. One aspect of the service plan was to work with the local ambulance trust to gather data around patients using ambulance services for hypoglycaemia, and to provide an advisory service for individuals post ambulance call‐out. This audit identified 388 diabetic emergency ambulance call‐outs locally (for the period 1 September 2010 to 31 March 2011) including those for hypoglycaemia in the Leicester City area. The new service commissioned by Leicester City included diabetes specialist nurse assessment within two working days for all hypoglycaemic individuals accessing ambulance services. A care pathway was drawn up and agreed over a series of meetings between the Intermediate Care Diabetes Service and ambulance service leads. Copyright © 2013 John Wiley & Sons. Practical Diabetes 2013; 30(4): 151–153